Long-Term Effectiveness of Guided Self-Help for Parents of Children With ADHD in Routine Care—An Observational Study. Issue 2 (January 2021) - Döpfner, Manfred; Liebermann-Jordanidis, Hannah; Kinnen, Claudia; Hallberg, Nora; Mokros, Laura; Benien, Nicole; Mütsch, Anna; Schürmann, Stephanie; Wolff Metternich-Kaizman, Tanja; Hautmann, Christopher; Dose, Christina
Objective: To assess long-term effectiveness of guided self-help for parents of children with ADHD under routine care conditions.Method: 6- to 12-year-old children diagnosed with ADHD were enrolled in an observational study on a 1-year telephone-assisted parent-administered behavioral intervention. N = 136 families who completed the intervention participated in a follow-up assessment. Pre-, post-, and follow-up data were analyzed by repeated measures ANOVA with planned contrasts. Clinical significance was analyzed according to the reliable change index.Results: Child ADHD symptoms (primary outcome), oppositional defiant disorder (ODD) symptoms, overall behavioral problems, and quality of life improved during the intervention. There was a further improvement in ADHD symptoms at follow-up, with a medium effect size. Improvements during treatment in ODD symptoms, overall behavioral problems, and quality of life were maintained at follow-up.Conclusion: The findings suggest that telephone-assisted self-help interventions may result in a long-term reduction of child behavior problems.